ANALISIS TINGKAT KECEMASAN SISWA KELAS VIII DALAM PEMBELAJARAN SENAM LANTAI GULING LENTING - Gusti Ayu Nyoman Wini Arti .; Prof. Dr. I Nyoman Kanca, M.S. .; I Gede Suwiwa, S.Pd., M.Pd. . (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2017)
ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui penyebab munculnya kecemasan siswa kelas VIII dalam pembelajaran senam lantai guling lenting Smp Negeri 4 Sukasada Tahun Pembelajaran 2017/2018. Subjek penelitian ini adalah 54 orang siswa, terdiri dari 31 orang siswa laki-laki dan 23 orang siswa perempuan. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan menggunakan metode survey.Teknik pengumpulan data karakteristik dan kecemasan siswa menggunakan angket kemampuan dan kuesioner Hamilton Anxiety Rating Scale (HARS). Hasil analisis menunjukkan bahwa gejala-gejala kecemasan yang dialami siswa antara lain; perasaan ansietas (48 orang siswa), ketegangan (51 orang siswa), ketakutan (51 orang siswa), gangguan tidur (48 orang siswa), gangguan kecerdasan (46 orang siswa), perasaan depresi (46 orang siswa), gejala somatik otot (39 orang siswa), gejala somatic sensorik (44 orang siswa), gejala kardiovaskular (46 orang siswa), gejala respiratori (50 orang siswa), gejala gastrointestinal (39 orang siswa), gejala urogenital (53 orang siswa), gejala otonom (52 orang siswa), dan gejala tingkah laku pada wawancara (54 siswa). Tingkat kecemasan yang dialami oleh siswa antara lain; kecemasan dengan kategori tidak ada (0 - 14) hingga tingkat ringan (15 - 20) adalah masing-masing dialami oleh 1 siswa (2%) dari total 54 orang keseluruhan siswa. Kecemasan tingkat sedang (21 - 27) dialami oleh 3 orang siswa (6%). Kecemasan tingkat berat (28 - 41) dialami oleh 9 orang siswa (17%). Serta, kecemasan sangat berat (42 - 56) dirasakan oleh 40 siswa (74%). Kata Kunci : deskriptif kuantitatif, kecemasan, senam lantai, guling lenting ABSTRACT The aims of this study were to analyze the anxiety, especially to know about some indications and anxiety level of students grade VIII of SMP Negeri 4 Sukasada in Academic Year 2017/2018. The subjects of this study were 54 students, consisting of 31 males and 23 females. This study was a descriptive quantitative and made use of survey method. The data of student’s characteristics and anxiety in this study were obtained through the use of data elicitation and questionnaire of Hamilton Anxiety Rating Scale (HARS). The result of the analysis showed that the indications or anxiety symptoms of the students can sequentially be presented as follows; feeling of anxiety (48 students), tension (51 students), fear (51 students), sleep disorder (48 students), intelligence disorder (46 students), feeling of depression (46 students), somatic muscle symptoms (39 students), sensory somatic symptoms (44 students), cardiovascular symptoms (46 students), respiratory symptoms (50 students), gastrointestinal symptoms (39 students), urogenital symptoms (53 students), autonomic symptoms (52 students), and behavioral symptoms in the interview (54 students). The anxiety level of the students, such as the anxiety of zero level (0 - 14) until light level (15 - 20) are similar in number, which are each of them experienced by 1 student (2%) out of the whole 54 students. Moderate level of anxiety (21 - 27) experienced by 3 students (6%). Severe level of anxiety (28 - 41) experienced by 9 students (17%). And also, the most severe level of anxiety (42 - 56) experienced by 40 students (74%). keyword : descriptive quantitative, anxiety, gymnastic, kip-up roll